Prevalence and Effectiveness of Derivatives Usage among Listed Nonfinancial Malaysian Firms - Lee, Simmon Kok Hui (2014)
Derivatives had been a ‘dirty’ word among financial markets ever since the Financial Crisis of 2007-2009. Since then, there has been increased fear among managers that derivatives may cause more harm than good to their firms. Financial authorities and standard setters have rushed to implement more stringent and transparent requirements for the reporting of derivative positions in firms’ financial statements. It is important for managers to realize the positive potential from using derivatives as part of corporate financing and hedging activities. The prevalence of derivatives usage among Malaysian firms is found to be very low compared to developed countries. To increase derivatives usage in Malaysia, this research evaluates the performance of current derivative using firms against firms of similar industry that do not use derivatives via salient performance measures desirable by managers. The usage of derivatives was found to have a positive impact on overall firms’ profitability with derivative users enjoying higher returns on assets, but derivative users also found to have lower operating profit margins. No positive impacts were found for the financial position of firms. In terms of market performance, derivative users enjoy much higher firm valuation where their market to book value is significantly larger than that of firms that do not use derivatives. However, abnormal returns were lower for derivative users with the possible influence of the small firms’ effect. Sectors-wise, firms operating in the technology industry were found to have benefited the most from using derivatives while industrial product firms did not reap any advantages. Although there is no clear positive results from derivatives usage as intended, several explanations are posited including derivatives usage efficiency and small firms’ effect. It is important that firms’ managers are knowledgeable to minimize basis risks and hedge their exposures correctly.